UN peace operations and Asian security - Anthony, Mely Caballero-; Acharya, Amitav (Routledge, 2005)
Mely Caballero-Anthony is Assistant Professor at the Institute of Defence and Strategic Studies, Singapore. Her research interests cover regionalism and regional security in Asia Pacific, human security and conflict resolution. She has written extensively on ASEAN, ARF, UN Peace Operations, NGOs in Southeast and on politics and security in Malaysia and the Philippines. Her latest publications include: "Regionalisation of Peace in Asia", in Michael Pugh and WPS Sidhu, eds. The United Nations and Regional Security, (Lynne Rienner, 2003), Regional Security in Southeast Asia: Beyond the ASEAN Way